Public Good Provision in Indian Rural Areas : The Returns to Collective Action by Microfinance Groups - Casini, Paolo; Vandewalle, Lore; Wahhaj, Zaki (World Bank, Washington, DC, 2015)
Self-help groups (SHGs) are the most common form of microfinance in India. The authors provide evidence that SHGs, composed of women only, undertake collective actions for the provision of public goods within village communities. Using a theoretical model, this paper shows that an elected official, whose aim is to maximize re-election chances, exerts higher effort in providing public goods when private citizens undertake collective action and coordinate their voluntary contributions towards the same goods. This effect occurs although government and private contributions are assumed to be substitutes in the technology of providing public goods. Using first-hand data on SHGs in India, the paper tests the prediction of the model and shows that, in response to collective action by SHGs, local authorities tackle a larger variety of public issues, and are more likely to tackle issues of interest to SHGs. The findings highlight how the social behavior of SHGs can influence the governance of rural Indian communities.